Risk based analysis for detention pond overflow at Iskandar Malaysia (Nusajaya), Johor - Suif, Zuliziana (2008)
Overflow risk of detention pond is defined as the probability of having a rainfall event that produces a runoff volume more than the available storage capacity of detention pond. Overflow risk analysis depends on the waiting period (elapse time) and draining time. This study dealt with risk analysis of detention pond overflow at Ledang Heights, Nusajaya, Johor Bahru. Monte Carlo simulation the simplest application to estimate the probability of occurrence of the 10 year rainfall interevent timeswas applied during this study. The maximum value for interevent time was 8 hr and 6 hr occurred with probability 24.18% and 28.39% after 5000 and 10000 trials respectively using Gamma distribution. The most likely range for interevent time were 2 to 18 hr (1.34%-1%) and 2 to 22 hr (3.84%-0.05%). The equation by Guo (2002) was applied during this study. The highest overflow risk obtained was 0.425 for the longest drain time of 71.75 minutes and for shortest elapse time. The overflow risk increases as the drain time increases and the elapse time decreases. Therefore, the selection of a proper drain time (recession time) is very important for reducing risk of overflow. Size of detention pond at the site is 70 m length x 70 m width x 3 m depth. The new size suggested was 82 m length x 70 m width x 3 m depth. The storage capacity of detention pond was larger than the volume of maximum rainfall data. The new size of detention pond is appropriate at the area because it could collect the maximum volume of runoff over a longer time period at the lowest overflow risk. It is suggested to design at lower elapse and drain time to minimize the overflow risk.